(untitled) - K M Heal [et al.] (New York, 1996)
This book introduces the many ways that the Maple V system can be used to solve mathematical problems. Beginning with an overview of Maple's interactive worksheets and their features for documenting work, it goes on to present some of Maple's basic capabilities, including algebraic, high precision numeric, and graphical computing. After discussing the basic Maple expressions and data types and how expressions can be manipulated, the tutorial goes on to use a selection of Maple's thousands of commands to develop solutions to actual math problems. It includes examples on working with graphics, including two and three dimensional plots and animations, and how to combine graphical objects. Facilities for algebraic simplifications are discussed as a lead-in-to sample applications
Keywords: computer science - mathematics,maple ( computer programs )